2008
DOI: 10.1002/jsfa.3159
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of soybean meal with high and low glucosinolate rapeseed–mustard cake as protein supplement on performance of growing crossbred calves

Abstract: BACKGROUND: Feeding of high glucosinolate rapeseed-mustard cakes (RMCs) imparts adverse effects on dry matter (DM) intake, health and overall performance of animals. Recently, plant breeding efforts have resulted in many cultivars of RMCs containing low to moderate levels of glucosinolate in India. The feeding value of RMC cultivars with high and low glucosinolate was evaluated relative to commonly used soybean meal as a protein supplement in growing crossbred calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Similarly, Ravichandiran et al (2008) (Ward et al, 1993). Supplementing Cu from 0 to 30 mg kg −1 DM to a basal ration (7.5 mg Cu kg −1 DM) increased NDF digestibility in dairy cows (Zhang et al, 2007).…”
Section: Rumen Fermentation Nutrient Digestion and N Metabolismmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, Ravichandiran et al (2008) (Ward et al, 1993). Supplementing Cu from 0 to 30 mg kg −1 DM to a basal ration (7.5 mg Cu kg −1 DM) increased NDF digestibility in dairy cows (Zhang et al, 2007).…”
Section: Rumen Fermentation Nutrient Digestion and N Metabolismmentioning
confidence: 92%
“…Many studies showed that the end products of GLS in vivo negatively affected growth performance of animals by reducing feed intake, affecting thyroid function and damaging the liver and kidneys (Dillard et al, 2018;Ravichandiran et al, 2008). Ruminants are comparatively less sensitive to dietary GLS than monogastric animals (Tripathi & Mishra, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…acephala DC) to fattening lambs can increase the concentrations of T 3 and T 4 in serum (76). Feeding a diet containing a high content of GSLs to calves resulted in a quadratically increased serum T 4 concentration, although T 3 concentration remained within the normal physiological range (79). Diets contained GSLs affect thyroid function in many animal species (56), including pigs (80), mares (81), turkeys (82), hens (83), and turbots (84), suggesting that effects of GSLs on thyroid function are not unique to ruminants, but universal in a wide range of animal species.…”
Section: Effects Of Secondary Metabolites In Brassica Forages On Triimentioning
confidence: 99%
“…Feeding brassica forages or diets containing GSLs and their breakdown products can affect animal thyroid function and alter thyroid hormone secretion (56,(75)(76)(77)(78)(79). For example, feeding turnip (Brassica rapa L.) and kale (B. oleracea L. var.…”
Section: Effects Of Secondary Metabolites In Brassica Forages On Triimentioning
confidence: 99%